Response of gastrointestinal tract to Pasteurella multocida serotype B:2 infection in buffaloes (Bubalus bubalis Linnaeus) - Muhammad, Abubakar Salisu (2012)
Pasteurella multocida B:2, which causes haemorrhagic septicaemia (HS) of ruminants, is believed to enter the host via the respiratory tract. Among the consequences of the respiratory route of infection are septicaemia, increased permeability of blood vessels and presence of the organism in several organs. However, the respiratory tract may not be the only portal of entry and route of spread of P. multocida B:2. Circumstantial evidence had suggested the involvement of gastrointestinal tract in the pathogenesis of HS in ruminants. Nevertheless, the pathogenesis and pathology of the disease following oral infection has not been well documented since previous reports on the disease were limited to incidental observations. The response of gastrointestinal tract following oral exposure to P. multocida B:2 was studied and compared its severity with intratracheal exposure. The safety,antibody pattern and mucosal immune response in the gastrointestinal and respiratory tracts following oral or intranasal exposure to gdhA (glutamate dehydrogenase) derivative P. multocida B:2 in buffalo calves were also investigated. The clinical signs observed in this studies includes; dullness, depression,recumbency, pyrexia, dyspnoea, congested mucous membranes, nasal discharge, lacrimation and salivation following single oral exposure to P. multocida B:2, however mean clinical score were significantly higher in intratracheally exposed group, inaddition diarrhea was noted in group of calves exposed orally to P. multocida B:2 twice, 2 weeks apart. The pathological alterations as the result of oral or intratracheal exposure to P.multocida B:2 included generalized lymphadenopathy, acute ulcerative rhinitis, acute fibrinous pneumonia, pleurisy, hydropericardium, hydroperitoneum, haemorrhagic encephalitis, acute enteritis, colitis and necrotizing and haemorrhagic typhilitis and proctitis, however lesions scoring revealed higher scores in gastrointestinal following orally exposure,while respiratory tract showed higher scores in intratracheally exposed group. Following oral or intratracheal exposure, P. multocida B:2 was isolated from the intestinal segments of the calves that developed severe clinical HS and they had to be sacrificed at 48 h post-exposure. Similarly,the ultrastructural changes in the infected calves were typical of acute cellular injury, with degeneration of endothelium and vascular walls of the gastrointestinal and respiratory tracts. There were deciliation in the respiratory tract, and microvilli degeneration and disruption in the gastrointestinal tract. Scanning electron microscopy revealed P. multocida B:2 presence on the surfaces of oesophagus, nasal mucosa and trachea of calves in both oral- and intratracheal-exposed group. The lesions were confirmed through the immunoperoxidase technique, to be associated with the inoculated P. multocida B:2,. P. multocida B:2 antigen was detected not only in the bacterial clusters in the gastric pits, intestinal epithelia and capillaries, Brünner’s glands and crypt of Lieberkühn but also seen to interact with infiltrating neutrophils, macrophages and erythrocytes in congested vessels and in haemorrhages. Concurrently the mucosal-associated lymphoid tissue (MALT) response in the gastrointestinal and respiratory tracts of buffalo calves following oral exposure to live wild-type P. multocida B:2 was also evaluated. In calves exposed to both oral and intranasal P. multocida B:2, lymphoid nodules with increased sized and lymphocyte number were detected. With the confirmation of bronchus-associated lymphoid tissue (BALT) and gutassociated lymphoid tissue (GALT) involvement in P. multocida B:2 infection, an experiment was conducted to evaluate the safety, antibody pattern, and responses of BALT and GALT to exposure to gdhA derivative P. multocida B:2. Large dose oral and intranasal gdhA derivative P.multocida B:2 exposures elicited sustained and significantly higher serum IgG and IgA responses. Similarly, the IgG and IgA levels in bronchioaveolar fluid and intestinal washings were higher and the BALT and GALTresponses were significant. This study showed that P. multocida B:2 were present in various segments and tissues of the gastrointestinal tract following oral or intratracheal exposure. Therefore, it can be concluded that P. multocida B:2 infection can be transmitted via the gastrointestinal tract. Both oral and intranasal routes of administration of gdhA derivative Pasteurella multocida B:2 elicited high serum antibody response although mucosal IgA and IgG responses were variable. Thus, oral and intranasal infections with large doses of live attenuated P. multocida B:2 were safer than with wild-type P. multocida B:2. Both of these routes can be considered as potential alternative route for vaccine administration against HS in buffalo calves.